Analyzing the effects of social media influencers and advertising on consumer buying interests to determine the elasticity of digital marketing strategies - Amri; Febiansyah, Hidayat; Yulianti; Isnanto, Burham (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
By incorporating consumer behaviour theory and marketing communication theory, the research intends to investigate the impact of social media advertising and influencers on purchasing preferences and to evaluate the efficacy of digital marketing strategies. Data acquisition via online surveys and statistical analysis, including assessments of validity, reliability, normality, multicollinearity, heterogeneity, and double regression, are components of the research methodology. The findings indicate that purchasing interests are significantly and positively impacted by advertising and influencers; advertising and influencers account for 51.4% of the variance in purchasing interests. This research contributes to the body of knowledge by demonstrating how integrating influence and social media advertisements can increase the efficacy of digital marketing. Practical implications encompass the significance of discerning appropriate advertising and influencer strategies in order to augment consumer interest in making purchases. Additional investigation is warranted in order to comprehend the intricate interplay among social media, influencers, and consumer behaviour in the era of digitalization.